Examining the impacts of 12 weeks of low to moderate-intensity aerobic exercise on depression status in patients with systolic congestive heart failure - A randomized controlled study (Clinics, 2019)
OBJECTIVES: Psychiatric depression disorder is common in patients with systolic congestive heart failure (HF), and both conditions share underlying pathophysiological mechanisms. The incidence rate of depression disorder has clearly increased with the increase in HF manifestations in recent decades. Depression disorder is considered an independent predisposing factor for hospitalization, disturbed functional performance, and high rates of morbidity and mortality in HF patients. This randomized controlled study was designed to examine the impacts of low- to moderate-intensity aerobic exercise training on depression status in patients with systolic congestive HF. METHODS: A total of 46 systolic congestive HF patients with depression (40-60 years of age) were randomized to receive twelve weeks of mild- to moderate-intensity aerobic exercise plus standard medical treatment (exercise group) or standard medical treatment without any exercise intervention (control group). Depression status was examined using the validated Patient Health Questionnaire-9 (PHQ9) pre- and post-intervention at the end of the study program. RESULTS: No significant differences were observed between the exercise and control groups in demographic data or clinical characteristics (p40.05). Both study groups showed a significant reduction in depression status at the end of the 12-week intervention (po0.05). The comparison between the mean values of the depression scores showed significant differences between the two groups after 6 and 12 weeks of the intervention, indicating a greater reduction in depression scores in the exercise group than in the control group (po0.05). CONCLUSIONS: Twelve weeks of a low- to moderate-intensity aerobic exercise program was safe and effective for reducing depression severity in patients with systolic congestive HF. Low- to moderate-intensity aerobic training should be recommended for cardiac patients, particularly those with HF-related depression.